Effect of Plant Growth Regulators (IBA, BA, and CCC) on Some Flowering Characters of Three Hybrid Lily Cultivars of (Lilium spp. L.) - J. Attiya, Hatim; A. Naji, Dhuha; M. Askar, Hassan (Iraqi Journal of Science, 2023)
The present study was conducted in the nursery of Floriculture Unit, University of Baghdad in Iraq during September to December of 2013. Vernalized bulbs of hybrid lily cultivars were imported from the Netherlands. The experiments were included some hybrid lily cultivars which represent the main groups of lily (longiflorum hybrids, Asiatic hybrid and trumpet hybrids). The three lily cultivars named as Tiger (Oriental), Brunello (Asiatic) and White Heaven (Longiflorum) were sprayed two times, at five weeks after planting and at eight weeks after planting with a solution of Cycocel (100 mg /l), solution of Indole butyric acid (50 mg/l) and Benzyl adenine (50 mg /l). The results indicated that foliar spray with IBA lead to decrease in flower diameter in White heaven, increase in fresh and dry weight of bulbs and decrease the time required to flowering in Tiger Edition. BA led to increase in the time required for flowering and decrease in the flower number in Brunello, in Tiger Edition led to increase in dry weight of bulbs, while in White Heaven led to increase dry and fresh weight of bulbs with a decrease in flower diameter. While foliar spray with CCC led to increase in dry and fresh weight of bulbs and flower number in Tiger Edition, in Brunello led to increase in fresh weight of the bulbs and carbohydrate content of the bulbs ,in White Heaven led to increase in fresh and dry weight of the bulbs and carbohydrate content in bulbs..